RELIGIOUS TOLERANCE IN THE PERSPECTIVE OF GENERATION Z: THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN FOSTERING PLURALISTIC AWARENESS - Azis, Annisa Rahmania; Tamimi, Abdillah Rosyid; Kurjum, Mohammad (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
In Indonesia’s pluralistic society, religious tolerance is fundamental to maintaining harmony and sosial cohesion. However, rising cases of religious-based intolerance—particularly among youth—highlight the inadequate internalization of pluralistic values. This study explores the perspectives of Generation Z on religious tolerance and the strategic role of Islamic Religious Education (PAI) in fostering pluralism. Using a qualitative library research approach, this study analyzed scholarly literature from the past two decades to identify patterns connecting Generation Z’s characteristics, Islamic tolerance teachings, and educational strategies. The findings reveal that Islamic Religious Education (PAI) plays a strategic role in fostering a tolerant attitude in Generation Z through contextual and inclusive learning. By instilling the values ​​of justice, compassion, and human rights, as well as the role model of teachers, PAI forms the character of students who are empathetic and respect diversity.